Effect of silver nanoparticles incorporation on impact strength of Heat-cure denture base resins - Alla, Rama Krishna; Swamy, K N Raghavendra; Vyas, Ritu; Guduri, Vineeth; Tiruveedula, N. B. Prakash; Rao, G Narasimha (International Journal of Dental Materials, 2023)
Background: Poly (Methyl methacrylic acid) based materials are widely used for the fabrication of removable complete and partial denture prostheses. these materials are prone to fractures when subjected to impact forces. While recent studies have explored the antimicrobial potential of denture base materials incorporating silver nanoparticles, their impact on the mechanical properties crucial for the prosthesis's durability has not been adequately established.Aim: To evaluate the impact strength of the heat-cure denture base materials incorporated with various concentrations of silver nanoparticles. Materials and Methods: Silver nanoparticles were incorporated at various concentrations (0.5, 1.0, 2.0 and 5.0 wt%) into three different heat-cure denture base materials. A total of 150 rectangular-shaped specimens (50 x 6 x 4), which comprises 50 samples from each of the three heat-cure acrylic resins were made using the compression molding technique. Ten specimens (n=10) were allocated for each concentration such as control, 0.5wt%, 1.0wt%, 2.0wt% and 5.0wt% concentrations of silver nanoparticles. A “V” notch was made exactly at the centre of each specimen to prevent the ductile fracture. The impact strength was evaluated using the Izod impact tester. The data were subjected to One-way ANOVA and Post hoc tests for statistical analyses.Results: A decrease in the impact strength was observed in the modified groups compared to the control groups. One-way ANOVA showed significant differences (p=0.000) among the different concentrations of all three denture base materials.Conclusion: Silver nanoparticles incorporation reduced the impact strength of the denture base materials.